Home-Health-Aides Role in Preventing Pressure Ulcers of the Older Adults: a Scoping Literature Review - Sultana, Munira; Ehsan, Nazia; Zaman, Laila; Pinto, Jennifer; ShahidurRahman, A. K. M.; Ahsan, Mohammad Kamrul (Archives of Clinical and Biomedical Research, 2022)
The purpose of this scoping review was to explore the role of home-health-aides in pressure ulcer prevention for the older adults. Controlled vocabulary with a broad range of thesaurus was used to search databases (N=11) to retrieve sources (N=349). We included those sources (n=11) fulfilling all inclusion and exclusion criteria. All sources were charted and analyzed. The sources suggested that home-health-aides play four distinct roles: observing a client’s health condition (s); coaching clients and their informal caregivers; assisting healthcare providers such as physicians, nurses, physical therapists, occupational therapists, and dietitians; and reporting to the healthcare providers, clients and informal caregivers. We report four common themes in this review: Home-health-aides’ training; interdisciplinary care approach; their relationship with older adults; and their own beliefs on their care giving role. We conclude that the home-health-aides play a key role in pressure ulcer prevention and their roles need to be recognized.